2007
DOI: 10.1111/j.1399-0039.2006.762_7.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased frequencies of activating natural killer receptors are associated with liver injury in individuals who do not eliminate hepatitis C virus

Abstract: This study was designed to investigate the role of killer immunoglobulin-like receptor (KIR) genes in the outcome of hepatitis C virus (HCV) infection. In patients who cleared the virus (HCV RNA-) we found a decrease of 2DL2 (P= 0.04), and 2DS2 (P= 0.014) accompanied by an increase of 2DS5 (P= 0.04). Those RNA+ patients with elevated levels of hepatic transaminases (HCV RNA+ elevated alanine aminotransferase) showed an increased frequency of 2DS3 (P= 0.018). Additionally, in cirrhotic patients we found an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 9 publications
2
30
1
Order By: Relevance
“…Indeed, our analysis led to identification of a specific KIR haplotype in the centromeric haplotype block that is associated with chronic HCV infection in patients. This haplotype also included KIR2DL2, KIR3DL3, KIR2DS2, and KIR2DL1 genes, some of which have been found to be associated with chronic HCV infection in other studies (16,18). Indeed, because KIR2DL1 and KIR2DL2 both encode receptors that bind to HLA-C2 (32,44), these are possible candidate genes for explaining the increased risk of chronic infection associated with KIR2DS3 and HLA-C2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our analysis led to identification of a specific KIR haplotype in the centromeric haplotype block that is associated with chronic HCV infection in patients. This haplotype also included KIR2DL2, KIR3DL3, KIR2DS2, and KIR2DL1 genes, some of which have been found to be associated with chronic HCV infection in other studies (16,18). Indeed, because KIR2DL1 and KIR2DL2 both encode receptors that bind to HLA-C2 (32,44), these are possible candidate genes for explaining the increased risk of chronic infection associated with KIR2DS3 and HLA-C2.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells detect virally infected cells through KIR interactions with HLA class I. Several studies have investigated the role of KIR and HLA in HCV infection, but low sample numbers and heterogeneity of patient cohorts in terms of sex, age, ethnicity, route of infection, and HCV genotype have resulted in conflicting results (15)(16)(17). One larger study identified an inhibitory KIR gene, KIR2DL3, associated with resolution of HCV infection, and this was dependent on a homozygous HLA class I ligand background (11,18,19).…”
Section: −7mentioning
confidence: 99%
“…Interestingly, the homozygous expression of the inhibitory NK cell receptor gene KIR2DL3 and its ligands, the HLA-C group 1 alleles, correlate with clearance of HCV (40). In turn, the activating receptor gene KIR2DS3 is associated with elevated transaminases and seropositive HCV infection (41). Both studies suggest that reduced NK cell activity might have a beneficial impact on HCV clearance.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] While data on HCV sequelae in other indigenous peoples of the Americas are lacking, the possibility that inherited KIR gene profiles could contribute to these disease patterns is strengthened by the observation that similarities exist between the KIR gene profiles of this Aboriginal cohort and those reported in association with spontaneous clearance of HCV. 1,39,40 …”
Section: Current Kir Genetic Profiles May Reflect Historical Immune Smentioning
confidence: 99%